Application Of Criminal Sanctions Towards Children Who Are Suspects Of Meth Based On Law Number 35 Of 2014 Concerning Child Protection (Case Study Of Decision Number: 72/Pid.Sus-Anak/2023/Pn.Plg) - Bagus Oka Rayhan; Yusuf Hambali; Ismail Pettanase (Utan Kayu Publishing, 2025)
Legal protection for children who are being prosecuted for the abuse of methamphetamine is by providing special protection from the government and state institutions in the form of supervision, prevention, care, and rehabilitation by the government and the community. The formulation of the problem in this study is: 1. What is the legal protection for children who are being prosecuted for the abuse of methamphetamine? and. 2. How is the application of criminal sanctions against children who are suspects of methamphetamine based on Law Number: 35 of 2014 concerning Child Protection? The research method used in this study is normative research. The data sources used in this study consist of primary and secondary data. Based on the results of the study, it shows that: 1). Legal protection for children who are being prosecuted for the abuse of methamphetamine, children must be given special protection by both the government and special institutions, according to Article 3 of Law Number. 11 of 2012 concerning the Child Criminal Justice System which emphasizes that one of the rights of children is not to be arrested, detained, imprisoned except as a last resort. The rights mentioned in letter h of Article 3 are one of the fundamental rights that must be considered by Police and Court Investigators. 2). The application of criminal sanctions against children who are suspects of methamphetamine based on Law Number: 35 of 2014 concerning the Protection of Children who abuse narcotics can be carried out by diversion which is a very important policy to be applied in the formal justice process. In addition, children can also be subject to criminal sanctions which are a last resort. Criminal sanctions for children consist of principal and additional penalties. Principal penalties consist of warning penalties, penalties with conditions, job training, and coaching in institutions